1+2+4+...+2(n-1) = 2n - 1
Step 1. Prove for n = 1 (smallest n)
LHS = 1
RHS = 1
I.e. true for smallest n.
Step 2. Assume true for n = k, i.e.
1+2+4+...+2(k-1) = 2k - 1
Step 3. Prove true for n = k+1, i.e.
1+2+4+...+2(k-1) + 2k = 2k+1 - 1
LHS = 2k - 1 + 2k (since, from assumption, 1+2+4+...+2(k-1) = 2k - 1)
= 2.2k - 1
RHS = 2k+1 - 1
= 2.2k - 1 (whenever you have something to the power of k+1, you're multiplying it once more by the base)
= LHS, i.e. true for n = k+1 if true for n = k.
Therefore, since true for n=1, and true for n=k+1 if true for n=k, then true for n=2, n=3, etc.
I_F